THE EFFECT OF TOLL ROAD SPM SERVICE SUBSTANCE ON TOLL ROAD USER SATISFACTION IN THE JABODETABEK AREA - Desy Mei Dina Desy Mei Dina; Mawardi Amin (Jurnal Infrastruktur, 2023)
The purpose of this study is to find out the 8 (eight) service substance at minimum service standards which include road conditions, travel speed, accessibility, mobility, safety, rescue units, environment and rest areas and services that affect toll road user satisfaction. This study uses a questionnaire to toll road users, especially in the Jabodetabek area with the SEM-PLS method and the help of SMART-PLS. from the results and analysis of the data described, it is stated that there are 5 (five) service substance that have a negative relationship to the satisfaction of toll road users including road conditions, mobility, safety, environment, and service rest area. Then for the 3 (three) service substances that have a positive relationship to the satisfaction of toll road users, namely travel speed, accessibility and assistance units. This is shown from the results of road conditions to satisfaction obtained of 0.205, the value is <t-table 1.96, travel speed is 2.023 > t-table 1.96, accessibility is 3.216 > t-table 1.96, mobility is 0.916 < t-table 1.96, safety of 0.916 < t-table 1.96, aid units of 5.601 > t-table of 1.96, environment of 1.217 < t-table of 1.96 and rest and service area of 1.016 < t-table of 1.96 on user satisfaction